Payload Distribution and Gear Strength Analysis of Gear Meshing Process Under the Typical Contact Condition - Fu Shuangxue; Zhou Changjiang; Han Xu (Jixie chuandong)
In order to solve the tooth payload distribution and gear strength numerical simulation. Based on precise finite element model of gear,under two kinds of typical load contact condition of the static / quasi static load and dynamic contact load,the gear strength is simulated,and the conclusions are draw by comparison. 1The load is linear distribution along the contact line before running in and parabolic distribution after running- in,the influence of and the gear surface hardness,running- in effect and gear end stiffness effect on the load distribution are considered in numerical simulation of gear strength,and the simulation value is bigger than others. It is suitable for the numerical simulation of the gear strength before and after running- in. 2The stable running status gear is simulated under static payload conditions,the tooth root maximum stress values are close to the calculated values of empirical formulas. It is suitable for high precision gear strength numerical simulation. 3Due to the influence of shock effect,tooth surface friction is considered in the dynamic contact load gear strength numerical simulation,the simulation value is bigger than the calculated value of empirical formulas. It is suitable for the numerical simulation of the gear meshing impact. 4The stress concentration effect,gear tooth end face stiffness effect and the continuity of the elastomer force field are validated.